The Insight into the Role of Leptin and Its Receptor in Heart Failure with Preserved Ejection Fraction - Zabojska, Krystyna; Cygnarowicz, Aleksandra; Wojtas, Aneta Klaudia; Korotko, Urszula; Mandziuk, Aneta; Witowska , Kinga; Turemka , Mariola; Biskupski, Mikolaj; Hosseinnejad, Negar; Sacher, Karolina (Quality in Sport, 2024)
Heart failure with preserved ejection fraction (HFpEF) is a complex clinical syndrome with a multifactorial pathogenesis. Leptin, a hormone produced by adipose tissue, plays a key role in regulating energy balance, metabolism, and inflammatory processes. Its impact on the cardiovascular system is dualistic: on one hand, leptin can contribute to the development of HFpEF by promoting inflammation and metabolic dysfunction; on the other hand, it may exert protective effects by reducing body weight and enhancing metabolic functions. This literature review examines current data on leptin’s role in HFpEF, exploring both its detrimental and beneficial effects. The objective is to elucidate the mechanisms through which leptin influences the onset and progression of HFpEF, potentially guiding the development of more targeted therapeutic strategies.